2011
DOI: 10.1007/s00405-010-1478-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between metastasis-associated protein (MTA) 1 and lymphatic metastasis in tonsil cancer

Abstract: We evaluated immunohistochemically the expression profiles of metastasis-associated protein (MTA) 1 and their associations with lymph node metastasis in tonsil cancer. Immunohistochemical analysis of 43 tonsillar neoplasm tissues was performed using antibodies raised to MTA1. Depth of tumor invasion, lymph node metastasis, and clinical outcomes were assessed. Clinical N0 patients were divided into two groups: N0a, negative for MTA1; N0b, positive for MTA1. Occult node metastasis was reevaluated according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…In contrast, MTA1 expression in NSCLC (61/96, 63.5%) was significantly higher than that in adjacent normal lung tissues. Analyses of various tumor tissues have also found overexpression of MTA1 mRNA, or protein is correlated positively with the extent of tumor invasion or lymph node metastasis [7,[19][20][21]. Consistent with our research, its expression was can promote tumor cell proliferation, survival, migration/ invasion, and tumor angiogenesis and thus serves as a potent carcinogen.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, MTA1 expression in NSCLC (61/96, 63.5%) was significantly higher than that in adjacent normal lung tissues. Analyses of various tumor tissues have also found overexpression of MTA1 mRNA, or protein is correlated positively with the extent of tumor invasion or lymph node metastasis [7,[19][20][21]. Consistent with our research, its expression was can promote tumor cell proliferation, survival, migration/ invasion, and tumor angiogenesis and thus serves as a potent carcinogen.…”
Section: Discussionsupporting
confidence: 90%
“…For exophytic tumors, the measurement was taken from the height of the surface of the adjacent intact mucosa to the deepest point of infiltration 15. Depth of invasion was classified into 2 categories based on a 2 cm cut off, a modification from our prior study 16. The tumor growth pattern at the invasive front was assessed as either cohesive or non-cohesive, the former being a well-defined pushing margin with large tumor islands, and the latter consisting of scattered, small, irregular cords or single tumor cells with a poorly defined infiltrating margin 14,17.…”
Section: Methodsmentioning
confidence: 99%
“…Park et al reported that MTA1 can be a useful molecular marker to predict lymphatic metastasis in cancer of the tonsil showing immunohistochemical evidence delineating the expression profiles of MTA1 and their associations with lymph node metastasis in tonsil cancer. A significant correlation between the expression of MTA1 and lymph node metastasis along with MTA1 sensitivity of 53.3 % and a specificity of 84.6 % for the identification of cervical metastases was well defined [56]. 5.5 Differential MTA1 localization as a significant indicator for tumour progression Subcellular localization of coregulators always determines the extent of its activity.…”
Section: Tracking Mta1 In Laryngeal Carcinomasmentioning
confidence: 97%
“…Laryngeal carcinoma is strongly inclined to metastasis of the lymph nodes, which decreases both cure and survival rates [55]. Silencing of MTA1 reversed the behaviour of cancer of the larynx suggesting the therapeutic value of MTA1 in cancer treatment [56]. Park et al reported that MTA1 can be a useful molecular marker to predict lymphatic metastasis in cancer of the tonsil showing immunohistochemical evidence delineating the expression profiles of MTA1 and their associations with lymph node metastasis in tonsil cancer.…”
Section: Tracking Mta1 In Laryngeal Carcinomasmentioning
confidence: 98%